2021
DOI: 10.3389/fonc.2021.714536
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate NTCP Model of Hypothyroidism After Intensity-Modulated Radiotherapy for Nasopharyngeal Carcinoma

Abstract: ObjectiveTo evaluate the incidence of hypothyroidism in patients with nasopharyngeal carcinoma after intensity-modulated radiotherapy (IMRT), analyze its correlation with multiple influencing factors such as thyroid exposure dose, thyroid volume, and gender, and construct a multivariate-based normal tissue complication probability (NTCP) model for the occurrence of hypothyroidism after IMRT.Materials and MethodsThe thyroid hormone levels of patients at different points in time before and after radiotherapy wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 39 publications
(64 reference statements)
1
10
0
Order By: Relevance
“…Several clinical parameters, including age, sex, pre-existing thyroid disease, thyroid size, and radiation dose, have been associated with the development of RIHT. A prospective study identified mean radiotherapy dose to the thyroid and pretreatment thyroid volume as potential predictors of RIHT development [ 15 ]; these predictors were validated in subsequent studies on breast cancer and nasopharyngeal carcinoma [ 16 , 17 ], as well as in the present study. Interestingly, in the present study, the AUCs for these predictors were lower (although not significantly) than those for early post-treatment thyroid functioning volume.…”
Section: Discussionmentioning
confidence: 79%
“…Several clinical parameters, including age, sex, pre-existing thyroid disease, thyroid size, and radiation dose, have been associated with the development of RIHT. A prospective study identified mean radiotherapy dose to the thyroid and pretreatment thyroid volume as potential predictors of RIHT development [ 15 ]; these predictors were validated in subsequent studies on breast cancer and nasopharyngeal carcinoma [ 16 , 17 ], as well as in the present study. Interestingly, in the present study, the AUCs for these predictors were lower (although not significantly) than those for early post-treatment thyroid functioning volume.…”
Section: Discussionmentioning
confidence: 79%
“…Head and neck radiation therapy results in significant doses of radiation to the thyroid gland (10-80 Gy) because all or a large part of the thyroid gland is inside or near its (8). Factors such as gender, age, and thyroid volume affect hypothyroidism after radiation therapy, but radiation exposure to the thyroid is a proven risk factor (9). Ionizing radiation to the neck is a known risk factor for hypothyroidism, especially when exposed to it in childhood (2).…”
Section: Hypothyroidismmentioning
confidence: 99%
“…A total of 24 patients (34.8%) experienced hypothyroidism twelve months following radiation therapy. The incidence of hypothyroidism in individuals with NPC following RT was significantly influenced by the thyroid gland's volume and mean dosage (Dmean) (9).…”
Section: The Absorbed Dose Of the Thyroid Glandmentioning
confidence: 99%
“…Among them, Vx (referring to the percentage of thyroid volume exposed to a dose higher than xGy) is a dosimetric predictive parameter commonly used in many studies 16 21 . Additionally, researchers have developed NTCP models to predict RIHT and optimize the radiation dose for the thyroid based on risk factors 22 24 . However, relying solely on physical dose parameters from dose-volume histograms (DVH) may only provide partial information about dose distribution and lack information about voxel spatial relationships.…”
Section: Introductionmentioning
confidence: 99%